A rapid, sensitive, and widely applicable method for quantitative analysis of underivatized amino acids in different biological matrices by UHPLC‐MS/MS. Issue 20 (26th August 2019) - Guo, Na; Yang, Dawei; Yang, Xiaofang; Yan, Han; Fan, Bin; Dai, Jingang; Lei, Yan; Yan, Dan
Abstract: A rapid, sensitive, and widely applicable method for the simultaneous quantitative analysis of 20 underivatized amino acids in different biological matrices, including serum, plasma, and tissue homogenates, using ultra high performance liquid chromatography with tandem mass spectrometry was developed and validated. Only 4 µL of serum, plasma, or tissue homogenate was extracted with 996 µL of solution (1.7 mM ammonium formate in 85% acetonitrile containing 0.1% formic acid) containing 100 ng/mL phenylalanine‐d5 as an internal standard without any further derivatization step. In addition, the matrix effects were small because a large volume of extraction solution was used. The total run time including reequilibration was 13 min. The results of linearity, accuracy, repeatability, precision, limits of detection, limits of quantification, and sample stability were sufficient to allow the measurement of the amino acids in different biological matrices. We conclude that our method is rapid, sensitive, and widely applicable and represents an improvement over other currently available technologies.